Evaluation of the effect of patient position in the management of chronic heart failure patients presenting with dyspnea - Akpinar, Guleser; Topacoglu, Hakan (Journal of Surgery and Medicine, 2021)
Background/Aim: One of the pathomechanisms of congestive heart failure is inadequate cardiac load, and one of the physiological ways to reduce cardiac load is to decrease venous return. Based on this mechanism, we aimed to reduce venous return and alleviate cardiac load in patients by drooping their legs. In this study, we aimed to evaluate the impact of leg position on patients’ comfort and treatment, emphasize that patient position is valuable enough to be included in the treatment algorithm, and determine the effects of the patient sitting with legs hanging down position in an armchair (sitting position), or upright with the straight knees position on a stretcher with the stretcher’s head at 90°C (high Fowler’s position) on the patient’s perception of dyspnea in chronic heart failure (CHF). Methods: Patients over 18 years of age, followed-up with CHF diagnosis who presented to the emergency department (ED) with dyspnea were included in this case control study. The participants were divided into high Fowler’s and sitting groups. According to the Visual Analog Scale (VAS) scoring, patients were asked to point to the severity of dyspnea. Patients’ vital signs, 30-day mortality, and VAS scores were recorded at the 0th, 15th, 30th, and 60th minutes. Results: A total of seventy-four patients were included in the study. Thirty-eight patients in the high Fowler’s group, and thirty-six patients in the sitting group were treated. VAS started to decrease significantly at 15 minutes in sitting position. Although baseline VAS scores were higher at sitting than at the high Fowler’s position, the end of the 60th minute VAS scores and respiratory rate were significantly lower in the sitting group (P=0.016, and P=0.008, respectively). The mortality rate was significantly higher in the high Fowler’s group (P=0.028). Conclusions: We concluded that patient position plays a vital role in patients’ perception of dyspnea and mortality in the acute treatment of CHF patients presenting with dyspnea. Perception of dyspnea disappears earlier, and mortality is lower in the sitting position.